THE EFFECT OF ANDROID-BASED SMARTPHONE USE ON THE SIGNIFICANCE OF LEARNING ENGLISH IN SMPN 1 SIDRAP (International Journal of Education and Literature, 2023)
Effect of Application Usage “Hello English” Smartphone Based Android Against Upgrades Student Learning Outcomes in English Subjects in Middle School (Quasi-Experiments in Language Subjects English Class VII Students at Sidrap 1 Public Middle School) The research started with a lack of student learning outcomes with a percentage below 50% for English material, especially listening skills . Research done by using the experimental method. Planning is made such as using the Hello English Application based on Android and research instruments to support learning. The implementation of learning is passed properly starting from the initial activities (giving pretest questions), core activities (introduction, and use of the application Hello English) and closing activities (giving post test questions).  This shows that the use The Hello English application has the effect of increasing student learning outcomes in English subjects in junior high schools, specifically ability listening.